On the Financing and Investment Decisions of Multinational Firms in the Presence of Exchange Risk - Mehra, Rajnish (Journal of Financial and Quantitative Analysis, 1978)
Rajnish Mehra, On the Financing and Investment Decisions of Multinational Firms in the Presence of Exchange Risk, The Journal of Financial and Quantitative Analysis, Vol. 13, No. 2 (Jun., 1978), pp. 227-244